Pharmacological Sirt6 inhibition improves glucose tolerance in a type 2 diabetes mouse model. Issue 7 (6th April 2017) - Sociali, Giovanna; Magnone, Mirko; Ravera, Silvia; Damonte, Patrizia; Vigliarolo, Tiziana; Von Holtey, Maria; Vellone, Valerio G.; Millo, Enrico; Caffa, Irene; Cea, Michele; Daniele Parenti, Marco; Del Rio, Alberto; et al.
ABSTRACT: Sirtuin 6 (SIRT6) is a sirtuin family member involved in a wide range of physiologic and disease processes, including cancer and glucose homeostasis. Based on the roles played by SIRT6 in different organs, including its ability to repress the expression of glucose transporters and glycolytic enzymes, inhibiting SIRT6 has been proposed as an approach for treating type 2 diabetes mellitus (T2DM). However, so far, the lack of small‐molecule Sirt6 inhibitors has hampered the conduct of in vivo studies to assess the viability of this strategy. We took advantage of a recently identified SIRT6 inhibitor, compound 1, to study the effect of pharmacological Sirt6 inhibition in a mouse model of T2DM ( i.e., in high‐fat‐diet–fed animals). The administration of the Sirt6 inhibitor for 10 d was well tolerated and improved oral glucose tolerance, it increased the expression of the glucose transporters GLUT1 and ‐4 in the muscle and enhanced the activity of the glycolytic pathway. Sirt6 inhibition also resulted in reduced insulin, triglycerides, and cholesterol levels in plasma. This study represents the first in vivo study of a SIRT6 inhibitor and provides the proof‐of‐concept that targeting SIRT6 may be a viable strategy for improving glycemic control in T2DM.—Sociali, G., Magnone, M., Ravera, S., Damonte, P., Vigliarolo, T., Von Holtey, M., Vellone, V. G., Millo, E., Caffa, I., Cea, M., Parenti, M. D., Del Rio, A., Murone, M., Mostoslavsky, R., Grozio, A., Nencioni, A., Bruzzone S. Pharmacological Sirt6 inhibition improves glucose tolerance in a type 2 diabetes mouse model. FASEB J. 31, 3138–3149 (2017). www.fasebj.org